Spatial pattern of risky health behavior in India: evidence from recent National Family Health Survey 2015 - 16 - Abhishek Kumar (Tobacco Induced Diseases, 2018)
Background Association between risky health behavior (consumption of tobacco/alcohol) and lung diseases is well stablished. India is one the countries with increasing burden of lung diseases. Using the most recent evidence available in the country, this paper examines the spatial pattern of risky health behavior among men and women.